Prevalence of pressure injury among Chinese community‐dwelling older people and its risk factors: A national survey based on Chinese Longitudinal Healthy Longevity Survey - Cai, Ji‐Yu; Zha, Man‐Li; Yuan, Bao‐Fang; Xie, Qian; Chen, Hong‐Lin (Journal of advanced nursing, 2019)
Aim To investigate the distribution of pressure injuries among older adults in China and to identify the associated risk factors. Design Cross‐sectional study. Methods The identified subjects were collected from 2012 wave of a national Chinese Longitudinal Healthy Longevity Survey. Older people were defined as being 65 years of age or older. We used chi‐square test and binary logistic regression to investigate the risk factors of pressure injury development. Results A total of 55 older people were documented as suffering from pressure injuries among 6,961 older Chinese adults, with a prevalence of 0.8%. In the group of disability, the prevalence of pressure injuries from high to low was 3.6% in the highly limited group, 0.4% in the moderately limited group, and 0.3% in the not limited group. The prevalence of pressure injury among older people with stroke, cancer, and dementia were 2%, 4.2%, and 6.6%, respectively. According to the final binary logistic regression analysis, age, disability, incontinence, cancer, and dementia emerged as important risk factors for pressure injury development. Conclusion Pressure injury among Chinese community‐dwelling aged people was shown to be associated with age, disability, incontinence, cancer, and dementia. As the development of pressure injury may distinctly increase the burden on individuals and healthcare systems, the social and related institutions should actively prevent and control the disease. Impact The results of this study will improve the identification of pressure injury among older Chinese people and contribute to the development of effective pressure injury risk management interventions. 目的 在于探讨中国老年人压力性损伤的分布情况,并确定相关的危险因素。 设计 横断面研究。 方法 确定的受试者选自于2012年全国性中国纵向健康长寿调查。老年人是指65岁或以上的人群。我们使用卡方检验和二元逻辑回归来研究压力性损伤发展情况的危险因素。 结果 据记录,在6961名中国老年人中,共有55名老年人遭受了压力性损伤,发病率为0.8%。在残疾组中,高度受限组的压力性损伤发病率从高到低地为3.6%,中度受限组为0.4%,非受限组为0.3%。在患有中风、癌症和痴呆的老年人中,压力性损伤发病率分别为2%、4.2%和6.6%。根据最终的二元逻辑回归分析结果,年龄、残疾、失禁、癌症和痴呆成为压力性损伤发展情况的重要危险因素。 结论 中国社区老年人的压力性损伤与年龄、残疾、失禁、癌症和痴呆有关。由于压力性损伤的发展情况可能会明显增加个人和医疗保健制度的负担,社会和相关机构应积极预防和控制这类疾病。 影响 这项研究的结果将有助于识别中国老年人的压力性损伤和制定有效的压力性损伤风险管理干预措施。